The Effect of Additional Vermiculite on Compressive and Flexural Strength of Concrete - Syahril Syahril; Mujiman Mujiman; Desutama Prayogo; Muhammad Raihan Riandi; Lintang Dian Artanti; Ambrosio Martins Nuno (Widyagama University of Malang, 2023)
Concrete is one of the building materials that is used the most. The majority of the volume of concrete is made up of aggregates, which have a significant impact on the characteristics, mix proportions, and economics of concrete. The space created by the absence of fine aggregate can be filled with vermiculite. Vermiculite is a rich mineral that is widely recognized for its exfoliating properties and for expanding quickly when heated. Vermiculite typically has a temperature resistance of up to 1200°C. It is a system of low-density, non-structural building products. In addition to being lighter in weight and odorless, vermiculite offers increased workability, improved fire resistance, and improved resistance to cracking and shrinking also reduce cost of construction. In this research, vermiculite is employed at varying concentrations of 12%, 24%, and 36%. Vermiculite samples from PT.IPI Sunijaya, cement with the Dynamix brand, fine aggregate from the Galunggung area, and coarse aggregate from Cimalaka. The design of this research followed ACI 1991, with a design quality of 15 MPa. The maximum variant on compressive strength and flextural strength of concrete is using 36% of vermiculite because vermiculite has a high capacity for water absorption, adding it to concrete boosts both the compressive strength and flexural strength of the material. Vermiculite will therefore absorb excess water in the mixture and dry out the mortar while keeping the completed product's firmness owing to the granules. This is why it is added to and blended with concrete. Vermiculite particles can be used to patch cracks and holes in concrete.